Modern oriental corporate culture : A case collection - Su, Yong (Springer Berlin Heidelberg, 2014)
The book covers Oriental management theories as well as their applications; research on positivism; long-term focus; exclusive interviews and accumulating first-hand data, etc. It also addresses the following topics: Chinese family businesses that have survived for more than one hundred years(e.g. INFINITUS, Beijing TRT); Chinese enterprises and firms that follow the oriental management culture serve as the dynamic engines to the 2nd largest economic entity in the world (e.g., Huawei Technologies Co., Ltd., Mengniu Dairy Gr., Hainan Airlines and so on); Eastern and western managerial cultures that have been growing within Chinese businesses(e.g., Hainan Airlines, INFINITUS); Varied schools such as Confucianism, Taoism, Buddhism, legalism, Military Strategists, Mohist School remain vital but at the same time Chinese businesses and firms welcome and extract the essence of western managerial civilization rather than reject it, etc. These areas will be of particular interest to readers, and the purpose of the book is not only to acquaint the reader with China by providing information about Chinese businesses and firms, but also to provide a royal road to doing business with China as well as allowing them to learn about Chinese managerial wisdom.